2019
DOI: 10.5585/conssaude.v18n1.10609
|View full text |Cite
|
Sign up to set email alerts
|

Reprodutibilidade do método Cobb na medição da lordose lombar de crianças utilizando diferentes níveis vertebrais

Abstract: Introdução: A radiografia é o padrão ouro para avaliação da coluna vertebral. Contudo, apresenta uma variabilidade inerente ao exame e ao avaliador. Objetivos: (1) comparar os ângulos de lordose lombar utilizando diferentes níveis vertebrais de referência e (2) verificar a repetibilidade e a reprodutibilidade do método Cobb na avaliação da lordose lombar de crianças. Métodos: Participaram do estudo 50 crianças, idade de 11,5 ± 2,6 anos. Os exames foram avaliados de forma independente por três avaliadores utili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Similarly, in their study that evaluated a screening meter for assessing arterial hypertension, Bitencourt e Gottschall (Bitencourt & Gottschall, 2012) considered reproducibility as a parameter for validating an instrument. Sedrez et al (2019) used the Cobb method to measure lumbar lordosis in children, and they found excellent values when evaluating repeatability and reproducibility, showing that the efficacy of this method is comparable to that of topographic system. They also acknowledged the importance of experienced evaluators in obtaining reliable and efficient results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, in their study that evaluated a screening meter for assessing arterial hypertension, Bitencourt e Gottschall (Bitencourt & Gottschall, 2012) considered reproducibility as a parameter for validating an instrument. Sedrez et al (2019) used the Cobb method to measure lumbar lordosis in children, and they found excellent values when evaluating repeatability and reproducibility, showing that the efficacy of this method is comparable to that of topographic system. They also acknowledged the importance of experienced evaluators in obtaining reliable and efficient results.…”
Section: Discussionmentioning
confidence: 99%
“…We performed a cross-sectional study with a quantitative approach based on the methodology used by (Sedrez et al, 2016) and (Sedrez et al, 2019). The sample comprised 37 students aged 18 to 28 years (24 males and 13 females), who attended courses at the Ceres Campus of the Federal Institute Goiano (Instituto Federal Goiano) during the evaluation period.…”
Section: Methodsmentioning
confidence: 99%
“…This study was based on the methodology of Sedrez et al (2016Sedrez et al ( , 2019, which has a cross-sectional design with a quantitative approach. The research was carried out at Instituto Federal Goiano -Campus Ceres in a room properly equipped with the Vert 3D evaluation system by Miotec Equipamentos Biomédicos Ltda., located in Rio Grande do Sul, Brazil.…”
Section: Methodsmentioning
confidence: 99%